1953
DOI: 10.1037/h0093638
|View full text |Cite
|
Sign up to set email alerts
|

A psychological study of eminent psychologists and anthropologists, and a comparison with biological and physical scientists.

Abstract: This is the third and last monograph in a series of clinical studies of research scientists. The series of studies was designed to investigate the existence of relationships between life history, intellectual functions or personality characteristics, and the selection and pursuit of a particular science as a profession. The subjects of the study are men who were selected for their eminence in research, as judged by their peers. The data comprise verbatim life histories, discussion of the work of the men, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
114
1
4

Year Published

1967
1967
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 242 publications
(125 citation statements)
references
References 15 publications
6
114
1
4
Order By: Relevance
“…However, does this mean that hard work is all that is needed or that anyone can engage in the kind of hard work that will lead to Newton's creative breakthroughs? Second, Roe (1951Roe ( , 1953aRoe ( , 1953b found that outstanding achievement in science was predicted by the participants' capacity for endurance, concentration, and commitment rather than their level of intellectual ability. However, Roe's scientists were all high in intellectual ability to begin with.…”
Section: Ellen Winnermentioning
confidence: 99%
“…However, does this mean that hard work is all that is needed or that anyone can engage in the kind of hard work that will lead to Newton's creative breakthroughs? Second, Roe (1951Roe ( , 1953aRoe ( , 1953b found that outstanding achievement in science was predicted by the participants' capacity for endurance, concentration, and commitment rather than their level of intellectual ability. However, Roe's scientists were all high in intellectual ability to begin with.…”
Section: Ellen Winnermentioning
confidence: 99%
“…Research on creative visionaries, traditionally the "Great Men" of science, attempts to build an average portfolio of their unique type (Roe, 1953), psychological profile, and life-path (Gardner, 1994). For example, through a rich comparison of the lives of Pablo Picasso, Sigmund Freud, and Albert Einstein, among others, Gardner argues that exemplary creators enter a Faustian bargain that requires "masochism and unbecoming behavior towards others" (Gardner, 1994: 362).…”
Section: Conflict In Creative Workmentioning
confidence: 99%
“…O interesse investigativo se refere à preferência por atividades de reflexão e pesquisa científica, o gosto por conteúdos abstratos e teóricos. A associação entre filhos únicos e dedicação à ciência foi salientada em pesquisas anteriores (Bryant, 1987;Helson & Crutchfield, 1970;Roe, 1953). Porém, estes estudos não haviam verificado esta relação a partir da avaliação do interesse vocacional.…”
Section: Discussionunclassified
“…Por exemplo, um número maior do que o esperado de homens primogênitos foi encontrado na advocacia (Very & Prull, 1970), na medicina (Watkins & Savickas, 1990), ou dedicados à pesquisa científica (Helson & Crutchfield, 1970;Roe, 1953). Recentemente, surgiram evidências de que esta relação também é significativa para as mulheres.…”
unclassified